The distribution of excess liquidity in the euro area - Luca Baldo; Benoît Hallinger; Caspar Helmus; Niko Herrala; Débora Martins; Felix Mohing; Filippos Petroulakis; Marc Resinek; Olivier Vergote; Benoît Usciati; Yizhou Wang (European Central Bank (ECB), 2017)
Since 2008, excess liquidity - defined as the sum of holdings of central bank reserves in excess of reserve requirements and holdings of equivalent central bank deposits - has tended to accumulate in specific euro area countries and in a small, slowly changing group of credit institutions. Despite the stability of the concentration of excess liquidity in specific countries over time, the relevance of individual drivers has changed. First, risk aversion has played a much smaller role in explaining the concentration since 2013 than it did at the time of "flight-to-quality" phenomena in the period 2010-12. Second, the location of the relevant market infrastructures (i.e. central securities depositories, securities settlement systems and TARGET2 accounts) used by counterparties that sold assets to the Eurosystem has been a more important driver directing flows in the period 2015-16. In addition, the more recent concentration of excess liquidity is explained by the combination of a number of factors, such as banks following strict internal credit limits, investment incentives created by yield differences across the euro area and the "home bias" in euro area government bond holdings. Overall, the net cross-border flows of liquidity that resulted also determined TARGET2 balances. At the individual bank level, when controlling for banks' capital, non-performing loans, credit risk and profitability, excess liquidity holdings in relation to total assets are found to be higher for smaller and better-capitalised banks, and for banking groups with liquidity centralised at the head institution. In addition, participation in Eurosystem longer-term refinancing operations and deposit inflows are associated with liquidity accumulation. Finally, new regulatory initiatives such as the liquidity coverage ratio are explained to be creating incentives to hold or not to distribute liquidity, thereby affecting its distribution.
Keywords: D39; E41; E44; E50; G01; G28; 330; excess liquidity; financial structure; asset purchase programme; bank characteristics; regulatory changes